PENGARUH KOMPENSASI NON FINANSIAL, DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI DI KEMENTERIAN AGAMA KABUPATEN DONGGALA - Ardiana, I Dewa Putu (Fakultas Ekonomi Universitas Tadulako, 2018)
This study intends to determine and analyze simultaneous influence of non-financial compensation, work discipline, and motivation on the performance of employees in the Ministry of Religious; determine and analyze partial influence of non-financial compensation on the performance of employees in the Ministry of Religious; determine and analyze partial influence of work discipline on the performance of employees in the Ministry of Religious; determine and analyze partial influence of motivation on the performance of employees in the Ministry of Religious. Regression test results obtain sig. F value of 0.000 < 0.05, which can be interpreted that work discipline and motivation simultaneously have significant influence on employee performance; significance level of t-value of non-financial compensation of 0.798>0.05 can be interpreted that non-financial compensation partially has non-significant influence on employee performance; the significance level t-sig. of 0,007< 0,05 means that work discipline partially has significant influence on employee performance; the significance level t-sig. of 0.034 < 0.05 can be interpreted that motivation partially has significant influence on employee performance.